Pengaruh Bea Perolehan Hak atas Tanah dan Bangunan dan Pajak Bumi dan Bangunan Terhadap Pendapatan Asli Daerah Kota Yogyakarta - Sukma Naphasy Pamungkas (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine the effect of duty on the acquisition of rights to land and buildings and land and building tax on the city of Yogyakarta yogyakarta The nature of this research is quantitative research. Sources of data used are secondary data obtained from the Agency of Processing and Asset of the City of Yogyakarta. The population in this research is the acceptance of the duty of acquisition of land rights, building revenue and land and building tax and realization of PAD of Yogyakarta city. The sample used is the realization of the duty of acquisition of land and building rights, realization of land tax and building and realization report of PAD of Yogyakarta city. Data analysis in this research use multiple linear regression in SPSS vesi 16.0 program. The results showed that the value of F arithmetic 4.604 is greater than F table 2.90 with significance 0.00 <0.05. This shows that the acquisition of land and building rights (X1) and land and building tax (X2) has an effect simultaneously on PAD of Yogyakarta city. Persial taxes of the earth and buildings (X2) have a significant positive effect on the PAD of Yogyakarta. This is evidenced by significant significance at 0.027 <0.05 and t arithmetic of 2.320> 1.694, although the t value of 1.860> 1.694 is greater but the acquisition of land and building rights (X1) has no effect on the PAD of Yogyakarta. This is evidenced by the significance of 0.072> 0.05.